2017
DOI: 10.18203/2320-1770.ijrcog20174133
|View full text |Cite
|
Sign up to set email alerts
|

Complications of female sterilization procedure: review over a decade at district tertiary care hospital

Abstract: Background: Female sterilization is the most requested permanent contraceptive method worldwide and one of the most frequently performed elective, intra-abdominal surgical procedure in reproductive-age women. Even though considered as simple and safe procedure, complications do occur including death. Methods: The primary objective of the following study is to determine the demographic patterns of women presenting as sterilization complications and secondary is to evaluate possible etiological factors leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…12 In a study by Mule et al who also reported 84.6% of complications were of mini-laparotomy whereas in laparoscopic tubal ligation, complications were only 13.4%. 13 Wang et al demonstrated that interval and postpartum laparoscopic sterilization is a safe, simple and quick operation and appears to be superior to postpartum minilaparotomy in terms of complications. 14…”
Section: Discussionmentioning
confidence: 99%
“…12 In a study by Mule et al who also reported 84.6% of complications were of mini-laparotomy whereas in laparoscopic tubal ligation, complications were only 13.4%. 13 Wang et al demonstrated that interval and postpartum laparoscopic sterilization is a safe, simple and quick operation and appears to be superior to postpartum minilaparotomy in terms of complications. 14…”
Section: Discussionmentioning
confidence: 99%
“…GoI incorporated these directives into the revised quality standards, which also established a quality assurance mechanism and a revised compensation scheme for adverse events, should they occur [ 11 ]. Although this led to some improvements, public sector female sterilization services still did not meet the prescribed quality standards [ 12 , 13 ], resulting in an unacceptable number of deaths, complications, and failures [ 5 , 14 ]. In 2014, a major shift in the discourse around female sterilization took place when 16 women died after undergoing sterilization surgery in a family planning camp in the state of Chhattisgarh.…”
Section: Introductionmentioning
confidence: 99%